Precarity, food and accompaniment in community and youth work. Issue 2 (3rd May 2016) - Batsleer, Janet
Abstract : Based on an ethnographic study of community-based learning and youth work in Greater Manchester, between 2013 and 2014, the use of food both as a response to precarity and a means of precaritisation is explored. The term 'retrophilanthropy' is used to analyse the paradoxical existence of social relations in community-based projects which feed whilst creating social abjection and divisions between the deserving and undeserving (in the practice of food charity of Foodbanks). This is contrasted with more ambivalent relationships encoded in food through youth work, termed contract and reward; enterprise and creativity; personalist orientations; and proto-universalist. It is argued that some aspects of these offer a prospect of more democratic forms of socio-cultural accompaniment and even a glimpse of the possibility of a more equal relationship to food.